Acute cholinergic blockade with low dose pirenzepine reduces the insulin and glucose responses to a mixed meal in obese women with the polycystic ovary syndrome - Ismail, I.S.; Premawardhana, L.D.K.E.; Riad-Fahmy, D.; Miell, J.P.; Peters, J.R.; Scanlon, M.F. (Wiley, 1994)
Pirenzepine, a selective muscarinic cholinergic antagonist, reduces plasma insulin and plasma glucose responses to a mixed meal in a dose dependent fashion in normals and in patients with non-insulin dependent diabetes. We have studied the effects of pirenzepine on plasma insulin, plasma glucose, growth hormone (GH), androstenedione, testosterone, insulin-like growth factor- I (IGF-I) and IGF binding protein 1 (IGFBP-1) responses to a mixed meal in obese clinically hyperandrogenic women with the polycystic ovary syndrome. Six obese women with polycystic ovary syndrome (BMI range 27.3-39.8 kg/m²) were studied in random sequence, and received either placebo or pirenzepine (single doses of 50, 100, or 200 mg) one hour before a standard test meal. Blood was sampled every 15 minutes for 2 hours after the meal and every 30 minutes thereafter for a total of 4 hours. Mean fasting plasma insulin concentrations were increased. Peak post-prandial plasma insulin concentrations were reduced significantly by all three doses used. Post-prandial integrated plasma insulin concentrations were reduced by the two higher doses. Peak postprandial plasma glucose concentrations were also reduced. The late post-prandial GH surge was significantly suppressed by all three doses. However, plasma androstenedione, testosterone, IGF-I and IGFBP-1 concentrations were not significantly different when placebo was compared with pirenzepine 200 mg. Acute cholinergic muscarinic blockade with pirenzepine significantly reduces meal stimulated plasma insulin and plasma glucose concentrations in clinically hyperandrogenic women with polycystic ovary syndrome. The ability of pirenzepine to reduce plasma insulin without worsening glycaemia is a particular advantage and may be therapeutically relevant. Further studies are under way to assess the usefulness of pirenzepine in long-term suppression of plasma insulin in this group of patients.